2021
DOI: 10.1371/journal.pone.0249896
|View full text |Cite
|
Sign up to set email alerts
|

The Werther effect of celebrity suicides: Evidence from South Korea

Abstract: Since 2003 Korea has experienced the highest suicide rate among OECD countries. One of the societal risk factors that triggers suicide is the contagious nature of suicide. This paper empirically examines the effect of celebrity suicide reports on subsequent copycat suicides, using daily suicide data and information of highly publicized suicide stories in Korea from 2005 to 2018. The findings from the Poisson regression model suggest that the number of public suicides soars after media reports on celebrity suic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
3
17
1
1
Order By: Relevance
“…This study found that the risk of copycat suicide increased after the suicide of idol singer J and S. This is consistent with the results of existing studies regarding the presence of the Werther effect [9,22] and the increase in copycat suicides after celebrity suicides[6, 23,24]. A study by Jaehyun Kim(2013) claimed that after actor Choi Jin-sil committed suicide, the Werther effect was observed for eight weeks [7].…”
Section: Discussionsupporting
confidence: 89%
“…This study found that the risk of copycat suicide increased after the suicide of idol singer J and S. This is consistent with the results of existing studies regarding the presence of the Werther effect [9,22] and the increase in copycat suicides after celebrity suicides[6, 23,24]. A study by Jaehyun Kim(2013) claimed that after actor Choi Jin-sil committed suicide, the Werther effect was observed for eight weeks [7].…”
Section: Discussionsupporting
confidence: 89%
“…Stereotypes toward suicide may be rooted in culture and social media [28][29][30][34][35][36][37]. The evidence linking stereotypes toward suicide and the ideation-to-action framework suggests potential suicide prevention strategies for suicide-related researchers and educators.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have examined the roles of public media in influencing audiences into mimicking suicide after highly publicized incidences of suicide, which is known as the Werther effect [34]. People are tragically led by highly publicized suicidal stories and then try to conduct suicide by imitation [35,36]. The increasing popularity of social platforms raised concerns about suicide contagion, and the mechanism of suicide contagion is thought to be based on social learning [37].…”
Section: Introductionmentioning
confidence: 99%
“…Three dimensions have been identified for which social contagion appears to be a relevant explanatory framework in adolescent violence: the role of violent video games in aggressive behavior [ 11 ▪▪ , 12 ▪▪ , 13 ▪ ], the contagion of gun violence [ 14 ▪ , 15 ], and peer effects on bullying, cyber-bullying and violent offending [ 16 ▪▪ , 17 ▪▪ , 18 ▪ ]. Regarding adolescent mental health, although there are some studies that reference social contagion in relation to eating disorders [ 19 ▪ ] and alcohol interventions [ 20 ▪ ], most recent studies have focused on suicide [ 21 ▪▪ , 22 ▪ , 33 ▪▪ ].…”
Section: Introductionmentioning
confidence: 99%